Penggunaan Kalimat Efektif dengan Keterampilan Menulis Teks Deskripsi - Olin Nita (Jurnal Kajian Bahasa, Sastra dan Pengajaran (KIBASP), 2021)
This study aims to describe the relationship between effective sentences and the skills of writing descriptive texts for class VII students of SMP N 3 Kec. Payakumbuh. This type of research uses the quantitative correlation method. Sampling was done by random cluster sampling. The results showed that the students' average value of effective sentences was 73.59, with a more than adequate classification. The average descriptive text writing skill is 77.5, with good category. There is a correlation between effective sentences and writing the descriptive text for class VII students of SMP Negeri 3 Payakumbuh District with an r-value of 0.836, after being analyzed by the t-test formula, the value of t count> t table (4.02 > 2.085) with dk n-2 (22-2 = 20) and a significant level of 0.05 or 95%. In conclusion, there is a substantial relationship between effective sentences and the skills of writing descriptive text. The better the students' use of effective sentences, the better their writing skills, especially writing descriptive text. Keywords: Effective Sentences, Writing Skills, Description Text